Absence of Epidermal Antibodies in Stevens–Johnson Syndrome/Toxic Epidermal Necrolysis Patients but Beware of Single Positive Results - Gilles F. H. Diercks; Joost M. Meijer; Maria C. Bolling; Sonja M. H. J. Scholtens-Jaegers; Jeroen Bremer; Barbara Horvath (Dermatology Research and Practice)
Background. Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are rare and potentially life-threatening mucocutaneous blistering diseases that clinically can resemble autoimmune bullous diseases. Moreover, it has been shown that autoantibodies against epidermal proteins are present in SJS/TEN. Objectives. To establish the presence of antibodies against desmosomal and hemidesmosomal proteins in confirmed SJS/TEN patients. Methods. Serum of SJS/TEN patients diagnosed based on clinical criteria, e.g., epidermal detachment with erosions and severe mucosal lesions, (suspicion of) a culprit drug, and matching histologic results was evaluated by various techniques, e.g., indirect immunofluorescence on monkey esophagus, salt split skin and rat bladder, immunoblotting (IB) and immunoprecipitation (IP), ELISAs against desmogleins and BP180, keratinocyte footprint assay, and keratinocyte binding assay. Results. A total of 28 patients were included in this study, 15 men and 13 women with a mean age of 56 years. In most patients, none of the serological tests were positive. In two patients, an elevated DSG3 titer was found suspicious for pemphigus vulgaris. Three patients had elevated NC16a titers, suggesting bullous pemphigoid. However, in all these patients, no other tests were positive and in these patients, the biopsy for direct immunofluorescence showed no evidence for an autoimmune bullous disease. Three patients showed reactivity against rat bladder rat bladder; these were, however, completely negative for A2ML1, envoplakin, and periplakin in the IB as well as the IP. Conclusions. Serological analysis for desmosomal and hemidesmosomal antibodies is reliable to rule an autoimmune bullous disease in patients with suspected SJS/TEN. However, one should not rely on one single test method since false positive results can occur. Moreover, this study also makes it less plausible that antibodies against desmosomal and/or hemidesmosomal components are involved in the pathogenesis of SJS/TEN.